Benefits of domperidone in ambulatory acute diarrhea with severe vomiting - Irene A. O.; Achirul Bakri; Erial Bahar; Rusdi Ismail (Indonesian Pediatric Society Publishing House, 2007)
Background Recently, most patients with diarrheal disease (DD) cases are hospitalized not due to severe dehydration, but due to severe vomiting which interferes with fluid and food intake. Use of anti-vomiting medicines is not recommended because of its "central" side effects. Domperidone has prokinetic and antiemetic effects with only minimal extrapyramidal side effects. Objective To evaluate domperidone in preventing hospitalization of DD patients in outpatient setting. Methods This randomized double blind, placebo-controlled clinical trial, was conducted from February to August 2005 at Mohammad Hoesin Hospital, Palembang. We included patients aged 6 to 59 months old with acute diarrhea who had vomited at least 4 times in the last 24 hours, not in need of hospitalization, and agreed to participate. We excluded patients who had taken anti-vomiting drug, or those who had severe diseases, including severe malnutrition. The dose of domperidone was 1.25 mg per 5 kg body weight. Results There were 183 subjects randomized, consisted of 91 who took domperidone (treatment group) and 92 who took placebo (control group). The duration and decrease of vomiting frequency were significantly different in favor of domperidone. Domperidone prevented hospitalization significantly (P=0.001, OR=4.1, ARR = 20%, RRR=71%, NNT=5). No overt acute clinical side effects were found. Conclusion Domperidone significantly shortened the duration and decreased the frequency of vomiting in DD cases.